2015
DOI: 10.1007/s00170-015-7337-2
|View full text |Cite
|
Sign up to set email alerts
|

Parametric design optimization of hard turning of AISI 4340 steel (69 HRC)

Abstract: Abstract:Continuous research endeavors on hard turning (HT), both on machine tools and cutting tools, have made the previously reported daunting limits easily attainable in the modern scenario. This presents an opportunity for a systematic investigation on finding the current attainable limits of hard turning using a CNC turret lathe. Accordingly, this study aims to contribute to the existing literature by providing the latest experimental results of hard turning of AISI 4340 steel (69 HRC) using a CBN cutting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…The similar conclusion was discussed in the work of Das et al [7]. Rashid et al [8] used L 16 orthogonal array design concept of Taguchi method for four factors associated with four levels to optimize machining parameters (v, f, d) while hard turning of AISI 4340 steel (69 HRC) with cubic boron nitride tool. Conclusion revealed that lower feed produces improved machined surface finish, but causes high tool wear, so the choice of a suitable feed must be determined by trade-off between the quality and cost consideration.…”
Section: Introductionsupporting
confidence: 62%
“…The similar conclusion was discussed in the work of Das et al [7]. Rashid et al [8] used L 16 orthogonal array design concept of Taguchi method for four factors associated with four levels to optimize machining parameters (v, f, d) while hard turning of AISI 4340 steel (69 HRC) with cubic boron nitride tool. Conclusion revealed that lower feed produces improved machined surface finish, but causes high tool wear, so the choice of a suitable feed must be determined by trade-off between the quality and cost consideration.…”
Section: Introductionsupporting
confidence: 62%
“…Because surface roughness affects several functional attributes such as corrosion resistance, tribological characteristics, fatigue strength, and wear resistance of machined components, various researchers have employed methods which includes experimental, statistical, and analytical approaches in hard turning operation with various workpiece materials [18CrMo4, 42CrMo4, SEA8620, AISI 1040, 1045 for modeling and optimization using response surface methodology (RSM) (Elbah et al 2013;Hessainia et al 2013;Shihab et al 2014;Azam et al 2015;Meddour et al 2015;Bouzid et al 2015), Taguchi method (Gunay and Yucel 2013;Rashid et al 2016;Zerti et al 2016;Panda et al 2016;Das et al 2017a), ANN (Asiltürk and Çunkaş 2011;Pontes et al 2012;Asiltürk 2012;Mia and Dhar 2016), GRA (Sahoo and Sahoo 2013a;Kacal and Yildirim 2012;Senthilkumar et al 2014), GA (Batish et al 2014;Bouacha and Terrab 2016), and particle swarm optimization (PSO) (Stryczek and Pytlak 2014;Yue et al 2016) to attain the surface quality and dimensional finishing condition similar to costly cylindrical grinding. For example, Hessainia et al (2015) found that response surface methodology represents a powerful approach and can offer to scientific researchers as well industrial metal workers a helpful optimization procedure for various combinations of the workpiece and the cut material tool.…”
Section: Introductionmentioning
confidence: 99%
“…The dry hard turning tests were experimented by means of Taguchi L16 orthogonal array (OA) design which comprises of total 16 experimental runs of different combinations of process inputs such as cutting speed (v), feed (f) and depth of cut (d) respectively each at four levels [26,27,28,29]. The levels of depth of cut vary from 0.…”
Section: Cutting Parametersmentioning
confidence: 99%